66.2k views
4 votes
Solve the system by substitution.
x – 4y = -8
5у – 1 = x
Submit Answer

2 Answers

2 votes

Answer:

The solution is (-36, -7)

Explanation:

Since 5y - 1 = x, we can replace x in the first equation by 5y - 1:

5y - 1 - 4y = -8

Collecting like terms, we get:

y = -7

If y = 7, then by the second equation x = 5(-7) - 1 = -36

The solution is (-36, -7)

User Tony Friz
by
6.0k points
4 votes

Answer:

y = -7 and x = -36

Explanation:

x - 4y = -8

5y - 1 = x

→ Substitute 5y - 1 into x - 4y = -8

5y - 1 - 4y = -8

→ Simplify

y - 1 = -8

→ Add 1 to both sides

y = -7

→ Substitute y = -7 into 5y - 1

( 5 × -7 ) - 1 = -36

User Sayeem
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.